Morphological Aspects of Antennal Sensilla of the Rhodnius brethesi Matta, 1919 (Hemiptera: Reduviidae) from the Negro River, Amazon Region of Brazil - Simone Patrícia Carneiro Freitas; Laura Cristina Santos; Amanda Coutinho de Souza; Angela Cristina Verissimo Junqueira (Journal of Parasitology Research)
Studies conducted in river Ererê located in the left margin of Negro River, municipality of Barcelos, state of Amazonas, have confirmed that Rhodnius brethesi has as its natural habitat the palm tree Leopoldinia piassaba. By scanning electron microscopy, sensillum type was studied on the antennae of R. brethesi. The specimens used come from the field and laboratory colony. No differences were observed between R. brethesi and other Triatominae studied. In the R. brethesi antennas, differences were observed only between the antennal segments and in the dorsal and ventral portions. Trichobothria sensilla show a difference with a lamellar base, suggesting that this conformation of the base of the sensilla is a synapomorphic feature of the genus. Another important observation is that, considering that R. brethesi is a specialist, infesting only one type of palm tree, trichoidea sensilla may be involved with plant-derived odorants. The knowledge of such functions could benefit the understanding of the likely biological role of these structures in chemical communication and also provide basic information for future studies of niche recognition, since this species of triatomine is only found in the L. piassaba palm.